2004
DOI: 10.1111/j.1601-5223.2004.01844.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships among genotypes of worldwide collection of spring and winter ryes (Secale cereale L.) determined by RAPD-PCR markers

Abstract: Genetic similarities among 20 spring and 22 winter accessions of agronomically different ryes from fourteen countries were estimated by employing random amplified polymorphic DNA (RAPD) techniques. Cluster analysis of genetic distance data showed that 42 genotypes were readily classifiable into two main groups: spring and winter groups. Within the spring group, cultivars fell into a North European and an American-Chinese group. Cultivars of winter rye fell into four groups: Northern European, Russian, American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
28
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 23 publications
8
28
1
1
Order By: Relevance
“…The low correlation between genetic and geographic distances obtained, is in agreement with earlier analysis (Hagenblad et al, 2016), and can be explained considering that pollen transfer between cultivated rye fields may easily occur as a result of its wind-pollination mode thus requiring relatively high isolation distances as established for other cross-pollinated crops (e.g., 1000–1600 m for cabbage, cauliflower). This lack of correlation between genetic and geographic distances is also in accordance with previous assumptions that attribute both temporal and ecological isolation for shaping rye's genetic diversity (Ma et al, 2004) in deterrence to spatial or geographic isolation. Moreover, individual-based clustering methods (STRUCTURE and DAPC) applied to our data highlights that genetic diversity scattering does not follow a geographic trend, regardless of being cultivars or landraces.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The low correlation between genetic and geographic distances obtained, is in agreement with earlier analysis (Hagenblad et al, 2016), and can be explained considering that pollen transfer between cultivated rye fields may easily occur as a result of its wind-pollination mode thus requiring relatively high isolation distances as established for other cross-pollinated crops (e.g., 1000–1600 m for cabbage, cauliflower). This lack of correlation between genetic and geographic distances is also in accordance with previous assumptions that attribute both temporal and ecological isolation for shaping rye's genetic diversity (Ma et al, 2004) in deterrence to spatial or geographic isolation. Moreover, individual-based clustering methods (STRUCTURE and DAPC) applied to our data highlights that genetic diversity scattering does not follow a geographic trend, regardless of being cultivars or landraces.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies on the genetic diversity of rye accessions share common features, namely: lack of correlation between accessions and geographic origin and similar genetic diversity between landraces (i.e., ex situ ) and cultivars, which is indicative of a common genetic background, regardless of breeding level or geographical origin (Bolibok-Brągoszewska et al, 2014; Hagenblad et al, 2016; Parat et al, 2016; Targońska et al, 2016). Indeed, it was proposed that ecological and temporal isolation are key for shaping rye's genetic diversity rather than spatial or geographic isolation (Ma et al, 2004). A recent study has shown that, rather than distinction between landraces and cultivars, diversity patterns on rye seem to be related to the end use over time (Parat et al, 2016), uncovering a clear separation of rye for forage in the Mediterranean area and for grain in Northeast Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Rye was introduced into China from Turkey and later the species was into Japan. Ma et al (2004) found that American cultivars were more closely related to Chinese cultivars than to European cultivars and that temporal isolation had influenced the genetic diversity of rye more than geographical isolation.…”
Section: Discussionmentioning
confidence: 97%
“…Molecular techniques provide an alternative approaches for evaluating the genetic relationship in tree and crops. Since they are not subjected to environmental effects and are independent of the development stage of plant, these methods have been used to identify the germplasm of trees and crops (Ma et al 2004). They suggest that with the help of molecular markers it is possible to catalog trees, shrubs and crops for future conservation and further improvement of this species.…”
mentioning
confidence: 99%